RENAISANS PENDIDIKAN TINGGI ISLAM DI INDONESIA: PERAN UIN DALAM ERA MODERN - Armedi, Rama; Hafidz Imaduddin (IAI Sunan Giri Trenggalek, 2026)
This study explores the historical renaissance of Islamic education in Indonesia, which signifies a transformative era of holistic and integrative scientific development. Central to this movement is the institutional conversion of the State Islamic Institute (IAIN) into the State Islamic University (UIN). Employing a qualitative library research methodology, this inquiry analyzes diverse secondary sources, including scientific journals, academic texts, and credible digital archives. The findings indicate that the UIN system successfully produces graduates who are not only proficient in science and technology but also deeply rooted in Islamic scholarship. By implementing a paradigm of scientific integration, UIN positions itself at the forefront of the Islamic educational revival in Indonesia. Ultimately, this institutional evolution serves as a vital engine for developing human resources capable of navigating the complexities of the modern global landscape without compromising spiritual values.